Determinants of Fixed Asset Revaluation Decision and Its Impacts on Market Reaction: A Comparative Study in Indonesia and Singapore - Erni Suryandari Fathmaningrum; Satrio Kusumo Yudhanto (Journal of Accounting and Investment, 2019)
The purpose of this study is to examine the influence of firm size, fixed asset intensity, liquidity, leverage, declining cash flow from the operation, and its impact on market reaction. The population in this study is manufacturing companies in Indonesia and Singapore in 2015-2016 period. The sample in this research was taken using a purposive sampling method, a total of 228 manufacturing companies in Indonesia and 255 in Singapore were used as the sample. The data were analyzed using logistic regression and simple linear regression. The results showed that firm size, fixed asset, and leverage affected revaluation policy in Indonesia, while liquidity and declining cash flow from operation did not affect fixed asset revaluation policy in Indonesia. In contrast to what occurred in Singapore, the results showed that fixed asset intensity and leverage proved to affect fixed assets revaluation policy, and firm size, liquidity, and declining cash flow from operation variables did not affect the policy of fixed asset revaluation in Singapore. In addition, this study also found the effect of fixed asset revaluation on market reaction in Indonesia and Singapore. Finally, the study also found differences in the adoption of fixed asset revaluation policies in Indonesia and Singapore.